Disintegration behavior and improvement mechanism of guar gum modified red clay in dry and wet cycle - Binghui Zhang; Jiankun Hu; Ningshuan Jiang; Jicheng Xu; Donghua Han; Rui Duan; Jianrui Hu; Yanhua Xie (PLoS ONE, 2025)
As an improved agent, GG (Guar Gum) has been widely used in engineering reinforcement in recent years. To assess the potential of engineering applications in red clay areas, the study examined the disintegration behavior of red clay and the improvement effects of both pure and modified red clay containing 0.05%, 0.1%, 0.15%, 0.2%, and 0.25% GG under dry and wet cycle conditions. By quantifying the macroscopic mechanisms of GG’s impact on red clay and elucidating the microscopic mechanisms of GG’s improvement effects, the potential for engineering applications in red clay areas was confirmed. The experimental research results show that: (1) With an increase in GG dosage, the disintegration of red clay first decreases and then stabilizes, with the optimal improvement effect achieved at a GG dosage of 0.225%. (2) When the number of dry and wet cycles increases, the disintegration rate of GG-improved red clay increases less than that of unmodified soil. (3) Both macroscopic and microscopic improvement mechanisms show that GG can effectively improve the strength and stability of red clay by enhancing soil particles, improving particle grading, filling gaps, and forming GG kaolinite cementing bonds. In summary, GG has demonstrated great potential as an improved agent in engineering applications in areas with red clay. The research results enhance the understanding of the anti-disintegration behavior of red clay and provide a theoretical basis for improving soil engineering performance in areas with red clay.